Socio-emotional skills profiles and their relations with career exploration and perceived parental support among 8th grade students - Gamboa, Vítor; Rodrigues, Suzi; Bértolo, Filipa; Marcelo, Beatriz; Paixão, Olímpio (Frontiers in Psychology, 2023)
Socio-emotional skills can play a crucial role in students career development. This study used a person-centered approach to explore socio-emotional skills (curiosity, optimism, empathy, sociability, and responsibility) profiles among 8° grade students (N = 310). We also explored the relations of these profiles with career exploration (self and environmental), perceived parental support (emotional support, instrumental assistance, career-related modeling, and verbal encouragement) and school achievement. Using Latent Profile Analysis (LPA), four distinct profiles emerged that differed in terms of level and shape, namely: Other and Task oriented profile, Socio-emotional Adaptive profile, Socio-emotional non-Adaptive profile, Self- Oriented profile. Our results show that the “Socio-emotional Adaptive” profile can be clearly differentiated from the “Socio-emotional non-Adaptive” profile given the higher values it presents regarding all the variables in study. However, the differences between the “Other and Task Oriented” profile and “Self-Oriented” profile (intermediate profiles) were analyzed and discussed from qualitative point-of-view and adopting an exploratory approach. Overall, the findings of this study indicate that socio-emotional profiles have the potential to account for variations in career behaviors and academic performance. These results provide valuable insights for the development and implementation of career-oriented interventions targeted at 8th grade students and their immediate relational environments.